Hydrothermal formation of fibrous mineral structures: The role on strength and mode of failure - Vanorio, Tiziana; Chung, Jaehong; Siman-Tov, Shalev; Nur, Amos (Frontiers in Earth Science, 2023)
Studying the mechanisms that control the rheology of rocks and geomaterials is crucial to making predictions about geological processes and to functionalizing geomaterials. Understanding the control of structural arrangements at the micro and nano scale on physical and mechanical properties at the macroscopic scale is a tenet central to materials science but an area of rock physics still in its infancy. In this paper, we focus the attention on cementitious phases of rocks by studying the formation of micro- and nano-scale fibrous structures through hydrothermal synthesis, and the controls of their arrangements on mechanical properties. The laboratory experiments made use of the properties of hydrothermal water to promote the growth of fibrous mineral phases. These phases are characterized by nano-size diameter and length of a few microns, altogether creating disordered and entangled mats of fibrous bundles as those found in natural samples. We draw inferences from structural microscopy about the micro- and nano- structures of these fibrous phases to inform a statistical model that establishes an interdependence between structural parameters of fibrous structures and bulk mechanical response. Structural parameters include number and length of fibers, spatial orientation, and fraction of fibrous threads bearing the load. Mechanical properties include strength and mode of failure. We show that as the fibrous microstructure evolves from ordered and aligned to disordered and entangled, the mechanical response of the fibrous composite experiences a transition from brittle to ductile behavior. The disordered and entangled microstructure also exhibits lower strength at failure, but strength increases as the number of fibers within the microstructure increases. Furthermore, the longer the fibers, the larger the strain that the matrix can accommodate. The value of this study lies in further understanding fault healing through hydrothermal fluids and how the physical properties of fibrous microstructures resulting from it control brittle-ductile transitions, and possibly, slow slip events along subduction zones.